Efficient and selective N-, S- and O-acetylation in TEAA ionic liquid as green solvent. Applications in synthetic carbohydrate chemistry - Lafuente, María Leticia (2016)
Background: The ionic liquid triethylammonium acetate (TEAA) was found to be an efficient solvent in the acetylation of alcohols, amines, oximes and thiols to their corresponding acetyl compounds using only a 10% excess of acetic anhydride under mild conditions. Moreover TEAA is not only an inexpensive and recyclable solvent but also an anomeric selective catalyst in the per-O-acetylation of sugar moieties. Methods: Simple and effective organic synthesis protocols were provided for the selective acetylation of several substrates. The products were fully characterized by 1H and 13C NMR spectroscopy and the anomeric ratios were obtained from the 1H spectra. Results: Structurally diverse alcohols, phenols, thiols, amines, carbohydrates and oximes underwent acylation under mild conditions by this procedure to provide the corresponding acetates in excellent yields. TEAA ionic liquid is unique in its capability to act as both, solvent and high selective catalyst. As expected, the reaction proceeds with high b anomeric selectivity for sugars derivatives. Moreover, the ionic liquid was regenerated, recycled and reused for three times without apparent loss of reactivity and selectivity in all cases. Conclusions: The present procedure provides a powerful and versatile acylation method for alcohols, phenols, thiols, amines, oximes and carbohydrates. This protocol is endowed with several unique merits: selectivity, cost-efficiency, atom-economy and mild reaction conditions tolerable to acid sensitive functionalities. With these features, this method may be considered as a better alternative for the acetylation of a wide range of substrates.